2015
DOI: 10.1002/cyto.a.22629
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of molecule colocalization in bioimaging

Abstract: The quantitative analysis of molecule interactions in bioimaging is key for understanding the molecular orchestration of cellular processes and is generally achieved through the study of the spatial colocalization between the different populations of molecules. Colocalization methods are traditionally divided into pixel-based methods that measure global correlation coefficients from the overlap between pixel intensities in different color channels, and object-based methods that first segment molecule spots and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
151
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(153 citation statements)
references
References 58 publications
0
151
0
Order By: Relevance
“…Moreover, related books [4], [5] and special issues [6]- [9] include a few tutorial-style overview articles covering progress in recent years for a large variety of topics (e.g., tracking in fluorescence bioimaging [10]- [12], sub-diffraction limited imaging and single molecule localization [13], [14], parametric active contour-based image segmentation [15] ). Finally, several authors presented independently state of the art methods for specific and important topics including cell-shape analysis [16], neuron tracing [17], co-localization (percentage of co-detection of interacting protein types at the same location) [18], [19], 3D image deconvolution [20], spot detection [21] in fluorescence microscopy Even if it is generally a difficult task to present a broad view of activities in bio-image processing and analysis [2], several authors [22]- [25] already explained successfully how computer vision, image analysis and visualization algorithms combined in workflows, will play a significant role in image-based studies of cell biology.…”
Section: B Positioning and Paper Organizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, related books [4], [5] and special issues [6]- [9] include a few tutorial-style overview articles covering progress in recent years for a large variety of topics (e.g., tracking in fluorescence bioimaging [10]- [12], sub-diffraction limited imaging and single molecule localization [13], [14], parametric active contour-based image segmentation [15] ). Finally, several authors presented independently state of the art methods for specific and important topics including cell-shape analysis [16], neuron tracing [17], co-localization (percentage of co-detection of interacting protein types at the same location) [18], [19], 3D image deconvolution [20], spot detection [21] in fluorescence microscopy Even if it is generally a difficult task to present a broad view of activities in bio-image processing and analysis [2], several authors [22]- [25] already explained successfully how computer vision, image analysis and visualization algorithms combined in workflows, will play a significant role in image-based studies of cell biology.…”
Section: B Positioning and Paper Organizationmentioning
confidence: 99%
“…In the literature two categories of co-localization approaches are generally considered, which are either intensity-based or segmentation-based [18], [19]. The occurrence of yellow signals in an overlay fluorescence image generally depicts the correlation between the locations of the green and red signals in the cell, thus showing some co-localization between the two proteins under study.…”
Section: Spatio-temporal Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To reduce user bias and enhance quantitation, colocalization analyses can be automated through two basic approaches: pixel-based (signal overlap, intensity correlation), and object-based (spatial evaluation). 17 The latter is favored since it presents an opportunity for spatial exploration of the colocalized signal while being robust to noise and background fluorescence. 18 6 overall stress also increases but concentrated stress near the opening decreases, suggesting feedback between mechanical stress and wall deposition to reinforce the high stress area.…”
Section: Automated Detection Of Mts and Cscs Using Image Analysismentioning
confidence: 99%
“…Object-based measures of co-localization and nonlinear correlation metrics such as mutual information that have found widespread application in other fields may also prove valuable for extracting more subtle spatial relationships that are not captured by the linear Pearson and Manders' metrics. For example, Lagache et al [62] found that object-based Ripley's K-function for co-localization showed improved robustness to noise relative to Manders' and Pearson metrics when tested on dual-channel synthetic images with Gaussian noise. As new experimental techniques enable the recording of numerous molecularly specific channels, the adoption of multiple comparison procedures will be critical to examining many pairwise relationships in these multiplexed co-localization studies.…”
Section: Quantifying Molecular Co-localizationmentioning
confidence: 99%